The development of religious instruction in Philippine public schools - Reventar, Serafina E. 1913- (1960)
This paper presented the development of religious instruction as an optional subject in Philippine public schools, from the start of the American regime to the present. It analyzed the problem on the following phases: its philosophy and legal bases, and its implementation or status during the three periods- the American regime, the Commonwealth, and the Republic.
Thesis (M.A.)--University of the Philippines, Diliman.
Keywords: Religious education -- Philippines